Role of Essential Oils and Bioactive Components for Manufacturing Cosmetic Items - Aditi; Dabral, Kriti (Journal for Research in Applied Sciences and Biotechnology, 2023)
The cosmetics industry has been forced to search for new active chemicals as a result of increasing customer demand as well as stricter international regulations. Botanical extract offers a source of new active chemicals that is nearly endless and may be used to make cosmetics. Due to their olfactory character in the creation of fragrances and perfumes and the many beneficial properties of their individual components (EOCs), essential oils (EOs) are becoming increasingly popular natural ingredients in the cosmetics and toiletries industry. These properties include anti-inflammatory, antimicrobial, and antioxidant properties (e.g., moisturizers, lotions and cleanser in skin care cosmetics; conditioners, masks or antidandruff products in hair care products; lipsticks, or fragrances in perfumery). It is difficult to generalise the possible applications of essential oils in cosmetics and toiletries because each essential oil has its own unique chemical profile, which is connected with its own particular collection of benefits. Instead, formulators need to make an effort to discover acceptable mixes of essential oils or essential oil compounds in order to get the results they want from the completed goods. This paper presents a detailed examination of the existing research on the usage of essential oils and essential oil compounds (EOs and EOCs) in the cosmetics sector. In addition, we will focus on a few critical topics regarding the safety of essential oils and essential oil compounds used in the cosmetics sector. When formulators of cosmetics are working to perfect products that are based on botanical extracts, they are very likely to find the information offered in this review to be valuable.